2002
DOI: 10.1192/bjp.181.5.416
|View full text |Cite
|
Sign up to set email alerts
|

Conduct problems, gender and adult psychiatric outcome of children with attention-deficit hyperactivity disorder

Abstract: Girls with ADHD had a higher risk of adult psychiatric admission than boys. Conduct problems were also associated with a higher risk. Girls with ADHD with conduct problems had a very high risk of a psychiatric admission in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 19 publications
6
107
1
Order By: Relevance
“…[35][36][37] Disorders of this kind are among the most common psychiatric conditions in younger children and are associated with a range of comorbid conditions, including learning difficulties. 35,37,38 To conclude, in a large general population sample of preschool children, the prevalence of impairment in gross motor skills was higher among obese male children than normal-weight male children, whereas the prevalence of impairment in the ability to focus attention was higher in obese female children than normal-weight female children. The findings suggest that gender-specific associations between overweight and impairment in specific aspects of developmental functioning are evident in this younger population.…”
Section: Strengths and Limitationsmentioning
confidence: 86%
“…[35][36][37] Disorders of this kind are among the most common psychiatric conditions in younger children and are associated with a range of comorbid conditions, including learning difficulties. 35,37,38 To conclude, in a large general population sample of preschool children, the prevalence of impairment in gross motor skills was higher among obese male children than normal-weight male children, whereas the prevalence of impairment in the ability to focus attention was higher in obese female children than normal-weight female children. The findings suggest that gender-specific associations between overweight and impairment in specific aspects of developmental functioning are evident in this younger population.…”
Section: Strengths and Limitationsmentioning
confidence: 86%
“…Because a number of large prevalence studies have suggested that the male: female ratio of the disorder may be markedly lower than once believed, especially in adulthood (e.g., DuPaul et al, 2001;Kessler et al, 2005;Ramtekkar et al, 2010;Simon et al, 2009), research on ADHD in young women presents an urgent area of need (see also Gaub & Carlson, 1997;Gershon, 2002). Overall, girls with ADHD may be at particularly high risk for negative outcomes over time (see Babinski et al, 2011;Biederman et al, 2010Biederman et al, , 2012Chronis-Tuscano et al, 2010;Dalsgaard, Mortensen, Frydenberg, & Thomsen, 2002;Hinshaw et al, 2012).…”
Section: Adhd In Femalesmentioning
confidence: 99%
“…They have -even when in pharmacological treatment -much worse long-term outcomes than others who are comparable in terms of age and gender (Dalsgaard et al (2002); Mannuzza and Klein (2000)) and also when compared to siblings without ADHD (Currie and Stabile (2006); Fletcher and Wolfe (2008)). And although a series of randomized controlled studies show that treatment with central nervous system stimulants 1 is effective in terms of reducing ADHD core symptoms and improving social behavior (van der Oord et al (2008)), most studies only have very short follow up periods of up to three years after randomization implying that we effectively know very little about the longer-run consequences of treating children pharmacologically.…”
Section: Introductionmentioning
confidence: 98%